Novel Drug Delivery Systems for Phytoconstituents. - Gupta, Madhu; Chauhan, Durgesh Nandini; Sharma, Vikas; Chauhan, Narain Singh, 1950- (Milton : CRC Press LLC, 2019)
Novel Drug Delivery Systems for Phytoconstituents discusses general principles of drug targeting, construction material and technological concerns of different phytoconstituent in delivery systems. It focuses on the development of novel herbal formulations and summarizes their method of preparation, type of active ingredients, route of administration, biological activity and their applications. It dicusses therapeutic activities of plant derived chemicals, their limitations in clinical applications and novel drug delivery solutions to overcome them to provide better therapeutic effects with controlled and targeted drug delivery. Focus on drug delivery of phytomolecules Act as bridge between natural product scientist and clinical doctors Discusses mechanism of poor bioavailability of herbal molecules Increases awareness towards phytochemical efficacy Summarizes efficient novel delivery systems-based formulations. It extensively covers the applications of novel drug delivery systems including polymeric nanoparticles, solid lipid nanoparticles, nanostructured lipid capsules, liposomes, phytosomes, microsphere, transferosomes, and ethosomes. Some chapters are especially focused on anticancer phytodrugs, silymarin, andrographolide, berberine, and curcumin delivery with special emphasis on their application.
OCLC-licensed vendor bibliographic record.
Keywords: Drugs -- Controlled release; Drug targeting; Phytochemicals; Materia medica, Vegetable; HEALTH & FITNESS -- Herbal Medications; MEDICAL -- Pharmacology; MEDICAL -- Pharmacy